2020
DOI: 10.1093/mnras/staa2941
|View full text |Cite
|
Sign up to set email alerts
|

The MOSDEF-LRIS Survey: The connection between massive stars and ionized gas in individual galaxies at z ∼ 2

Abstract: We present constraints on the massive star and ionized gas properties for a sample of 62 star-forming galaxies at z ∼ 2.3. Using BPASS stellar population models, we fit the rest-UV spectra of galaxies in our sample to estimate age and stellar metallicity which, in turn, determine the ionizing spectrum. In addition to the median properties of well-defined subsets of our sample, we derive the ages and stellar metallicities for 30 high-SNR individual galaxies – the largest sample of individual galaxies at high re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
69
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 58 publications
13
69
5
Order By: Relevance
“…(O/Fe) to > 5 × (O/Fe) . A direct comparison to the Topping et al (2020b) results is shown in Fig. 9 where it can be seen that the basic result (i.e., g > ★ ) is fully consistent with the result presented here.…”
supporting
confidence: 86%
See 4 more Smart Citations
“…(O/Fe) to > 5 × (O/Fe) . A direct comparison to the Topping et al (2020b) results is shown in Fig. 9 where it can be seen that the basic result (i.e., g > ★ ) is fully consistent with the result presented here.…”
supporting
confidence: 86%
“…However, when interpreting the redshift evolution of emission lines, the known evolution towards more extreme H region conditions at high redshift must also be considered (e.g., Steidel et al 2014;Shapley et al 2015). Most recent results, as well as the results presented in this paper, suggest that the primary cause of this evolution is the harder ionizing spectra emitted by oxygen-enhanced, low-metallicity (i.e., iron-poor), stars at high redshift (e.g., Steidel et al 2016;Strom et al 2017;Topping et al 2020b, see Section 4.3 for further discussion). As a consequence, not all of the observed redshift evolution in line ratios can be attributed purely to changes in g (e.g., Cullen et al 2016).…”
Section: Trends With Emission-line Ratiosmentioning
confidence: 75%
See 3 more Smart Citations